Anomalous Pulmonary Venous Connection With an Intraparenchymal Course. (March 2017) - Campanale, Cosimo M.; Banka, Puja; Sanders, Stephen P.
An intraparenchymal course of the pulmonary venous pathway within one lung in anomalous pulmonary venous connection is a rare and poorly recognized variation. We report three new cases and summarize the remaining 19 known cases of this infrequent anomaly. We expect that this review will call attention to this unusual pattern of pulmonary venous drainage and enhance prospective diagnosis.